Pengetahuan dan Partisipasi Masyarakat Gampong Lamgugob Dalam Pencegahan Penyebaran COVID-19 - Siti Nur Zalikha; Hani Emafita (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This community service activity aims to provide knowledge and increase community participation in preventing the spread of COVID-19. The method used in this community service activity is carried out in two ways, namely 1) direct socialization to the community to use masks properly, live a healthy lifestyle and exercise 2) indirectly through social media of the local community. Socialization activities were carried out to the community of Lamgugob Village, Syiah Kuala District, Banda Aceh City. The results obtained from this community service activity are that the people of Lamgugop Village have sufficient knowledge and that the level of participation is quite high in preventing the spread of COVID-19. Keywords: Knowledge, Participation, COVID-19